(untitled) (Portuguese Journal of Family Medicine and General Practice, 2024)
Introduction: Cannabis is the illicit drug with the highest rate of abuse over a lifetime in Portugal. Although its medicinal use due to its antiemetic properties, a new and paradoxical clinical entity has been recognized – cannabinoid hyperemesis syndrome (CHS) – characterized by chronic cannabinoid consumption, cyclic episodes of difficult-to-treat nausea and vomiting, and compulsive hot showers for symptom relief. Case report: 36-year-old woman, with a history of multiple visits to primary health care center complaining about nausea and cyclic vomiting, still under investigation. She presented to the emergency department (ER) with complaints of epigastric pain, nausea, and vomiting for three days. Laboratory and imaging studies were carried out and did not show any significant alterations. Antiemetic medication and pantoprazole were given, with little improvement in the complaints. During her stay in the ER, she was found several times taking hot showers, repeatedly asking to do so, stating that it was the only measure that alleviated her complaints. In addition, a history of chronic cannabinoid use was found and consequently, the diagnosis of CHS was hypothesized. Comment: There is a common delay in the diagnosis of this syndrome, which leads to multiple hospitalizations, complementary diagnostic tests, and therapeutics. Thus, we aim to raise awareness of CHS among the medical community as a differential diagnosis of difficult-to-treat recurrent vomiting in individuals with a history of cannabinoid use. This case report aims to promote knowledge about CHS, enabling a timely identification and appropriate therapeutic approach to this diagnosis.